An Analysis of Code Switching and Code Mixing Used the the Characters in Novel Perahu Kertas by Dewi Lestari (Dee) - Yuniarta, Rizky; -, Wijayadi; Mayasari, Linda (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2014)
This research analyzes code switching and code mixing which exist in the conversation of novel Perahu Kertas. The aims of this research are describe the types of code switching and code mixing used in the conversation in novel Perahu Kertas, the components in speaking of code switching and code mixing in the conversation in novel Perahu Kertas, and the reasons of using code switching and code mixing. This research uses a descriptive qualitative with the conversation utterances in novel Perahu Kertas as the sample. The data collection technique in this research is documentation techniques. The data collection are taken from the conversation in novel Perahu Kertas that use code switching and code mixing. The source of the data of this research is utterances from conversations in the novel Perahu Kertas. Based on the analysis, the result can be concluded that the code switching and code mixing phenomena in novel Perahu Kertas are situational, metaphorical code switching, and inner, outer code mixing. The component of speaking is from SPEAKING acronym. The reasons of code switching and code mixing in novel Perahu Kertas are arrival of a new person, different status and formality, particular topics, affective message, and expressing disapproval.